E2F-2 Promotes Nuclear Condensation and Enucleation of Terminally Differentiated Erythroblasts - Swartz, Kelsey L. (Mol Cell Biol, 2016)
E2F-2 is a retinoblastoma (Rb)-regulated transcription factor induced during terminal erythroid maturation. Cyclin E-mediated Rb hyperphosphorylation induces E2F transcriptional activator functions. We previously reported that deregulated cyclin E activity causes defective terminal maturation of nucleated erythroblasts in vivo. Here, we found that these defects are normalized by E2F-2 deletion; however, anemia in mice with deregulated cyclin E is not improved by E2F-2-loss, which itself causes reduced peripheral red blood cell (RBC) counts without altering relative abundances of erythroblast subpopulations. To determine how E2F-2 regulates RBC production, we comprehensively studied erythropoiesis using knockout mice and hematopoietic progenitors. We found that efficient stress erythropoiesis in vivo requires E2F-2, and we also identified an unappreciated role for E2F-2 in erythroblast enucleation. In particular, E2F-2 deletion impairs nuclear condensation, a morphological feature of maturing erythroblasts. Transcriptome profiling of E2F-2-null, mature erythroblasts demonstrated widespread changes in gene expression. Notably, we identified citron Rho-interacting kinase (CRIK), which has known functions in mitosis and cytokinesis, as induced in erythroblasts in an E2F-2-dependent manner, and we found that CRIK activity promotes efficient erythroblast enucleation and nuclear condensation. Together, our data reveal novel, lineage-specific functions for E2F-2 and suggest that some mitotic kinases have specialized roles supporting enucleation of maturing erythroblasts.